Intervención educativa farmacéutica sobre el nivel de conocimiento en menopausia y terapia de reemplazo hormonal en mujeres de 35 a 65 años del centro poblado de Samne - provincia de Otuzco, mayo- julio 2011 - Castro Gutiérrez, Omar Yoel (2011)
The main goal of this research was determine the effect of pharmaceutical educational intervention on the level of knowledge in menopause and hormone replacement therapy in women aged 35 to 65 Samne- Otuzco, May - July 2011. Pharmaceutical educational intervention was spread through the distribution of leaflets and invitations addressed to women in the population study. Before the Pharmaceutical educational intervention we applied a survey, which allowed us to measure the level of knowledge in menopause and hormone replacement therapy. The results mirrored that of the 44 women in study, 31.8 per cent were at a low level, 68.2 per cent were in an intermediate and none was in a high level. Then, to carry out Pharmaceutical educational intervention in menopause and hormone replacement therapy, we used as educational tools some interactive type (survey questions), and information materials such as videos. After intervention, each assistant proceeded to fulfill the same opinion survey applied before like pre-test, results reflected that 75 % of women caught up with a loud level of knowledge after intervention. This significant difference ( p< 0.005 ) was checked by Student's t against the statistical proof, utilized for the difference of stockings. Concluding that the Pharmaceutical Educational Intervention managed to increase the level of knowledge in menopause and hormonal replacement's Therapy in women of 35 to 65 years of Samne-Otuzco, May- July 2011.